Phantasmatic Shakespeare : Imagination in the Age of Early Modern Science - Roychoudhury, Suparna (Book collections on Project MUSE., 2018)
"Examines the intersection of early modern psychology and the history of science. It argues that Shakespeare was primarily interested in imagination as a cognitive rather than an aesthetic power"--